Health seeking behavior among individuals presenting with chronic cough at referral hospitals in Uganda; Missed opportunity for early tuberculosis diagnosis - Muttamba, Winters (PLoS One, 2019)
BACKGROUND: Tuberculosis (TB) is the 9(th) leading cause of death from a single infectious agent. Patients live in a complex health care system with both formal and informal providers, and it is important that a TB diagnosis is not missed at the first interaction with the health care system. In this study, we highlight the health seeking behavior of patients and missed opportunities for early TB diagnosis for which interventions could be instituted to ensure early TB diagnosis and prompt TB treatment initiation. METHODS: This study was nested in a cross-sectional study that assessed the accuracy of different Xpert MTB/Rif implementation strategies in programmatic settings at the referral hospitals in Uganda. We documented the symptom profile of presumptive TB patients and assessed the health seeking behavior of those with chronic cough by calculating proportion of patients that visited each type of health facility and further calculated the odds of being TB positive given the type of health facility initially visited for consultation. RESULTS: A total of 1,863 presumptive TB patients were enrolled of which 979 (54.5%) were male, and 1795 (99.9%) had chronic cough. A total of 1352 (75.4%) had previously sought care for chronic cough, with 805 (59.6%) seeking care from a public health facility followed by private health facility (289; 21.4%). Up to 182 (13.5%) patients visited a drug store for chronic cough. Patients whose first contact was a private health facility were more likely to have a positive GeneXpert test (adjOR 1.4, 95% CI: 1.0–1.9; p = 0.047). CONCLUSIONS: Chronic cough is a main symptom for many of the presumptive TB patients presenting at referral hospitals, with several patients having to visit the health system more than once before a TB diagnosis is made. This suggests the need for patients to be thoroughly evaluated at first interface with the health care system to ensure prompt diagnosis and treatment initiation. Improved TB diagnosis possibly with the GeneXpert test, at first contact with the health care system has potential to increase TB case finding and break the transmission cycle in the community.